Engineered miniaturized models of musculoskeletal diseases. Issue 9 (September 2016) - Bersini, Simone; Arrigoni, Chiara; Lopa, Silvia; Bongio, Matilde; Martin, Ivan; Moretti, Matteo
Highlights: Miniaturized 3D in vitro models are effective tools to study musculoskeletal diseases. Main advantages: highly controlled conditions, low cell amount and hi-res real time imaging. Miniaturized osteochondral models allowed to characterize bone and cartilage pathologies. Muscular genetic and degenerative diseases have been investigated with miniaturized models. More advanced miniaturized models are needed to fully mimic pathologic environments. Abstract : The musculoskeletal system is an incredible machine that protects, supports and moves the human body. However, several diseases can limit its functionality, compromising patient quality of life. Designing novel pathological models would help to clarify the mechanisms driving such diseases, identify new biomarkers and screen potential drug candidates. Miniaturized models in particular can mimic the structure and function of basic tissue units within highly controlled microenvironments, overcoming the limitations of traditional macroscale models and complementing animal studies, which despite being closer to the in vivo situation, are affected by species-specific differences. Here, we discuss the miniaturized models engineered over the past few years to analyze osteochondral and skeletal muscle pathologies, demonstrating how the rationale design of novel systems could provide key insights into the pathological mechanisms behind diseases of the musculoskeletal system.